Is the internal training load different between starters and nonstarters volleyball players submitted to the same external load training? A case study - Thiago Andrade Goulart Horta; Danilo Reis Coimbra; Renato Miranda; Francisco Zacaron Werneck; Maurício Gattás Bara Filho (Universidade Federal de Santa Catarina, 2017)
The same training stimulus can provide different physiological adaptations for athletes of the same team. Thus, the aim of this study was to analyze and compare the load training of starters and nonstarters players, athletes of a men's volleyball team at different times of the season. The sample consisted of fifteen men's volleyball superleague athletes who were divided into two groups of starters and nonstarters players. The training load of the ten weeks of the team's preparation period for the main championship season in which no games were performed was selected for the study. The method of subjective perceived of effort (session-RPE) proposed by Foster et al. (2001) was used to quantify the training load. The group of starters players had higher total weekly training load (TWTL) and RPE values in the average of the ten weeks of training (p<0.05). Higher TWTL values for starters players in the preparatory and pre-competitive period compared to nonstarters players was also demonstrated (p<0.05). When different weeks were analyzed separately, weeks three and seven presented higher TWTL and RPE values for starters players compared with nonstarters players (p<0.05). The results presented in this study showed that starters players showed greater internal training load compared to nonstarters players.